2006
DOI: 10.1190/1.2213356
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of random wavefields: An interdisciplinary review

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
169
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(172 citation statements)
references
References 45 publications
2
169
0
1
Order By: Relevance
“…If the distribution of propagation directions is not isotropic the NCFs are asymmetric and represent a poorer approximation of the Green's function. Practically the coda of earthquake records and ambient seismic noise can be used as source wavefield for SI (Campillo 2006;Larose et al 2006) as was first demonstrated by Campillo & Paul (2003) and Shapiro et al (2005). By extracting surface waves (Brenguier et al 2007;Lin et al 2009;Stehly et al 2009) or body waves (Roux 2005;Tonegawa et al 2009;Zhan et al 2010;Poli et al 2012;Lin et al 2013;Nishida 2013) local, regional and global tomographic investigations of the subsurface velocity are among the most widely used applications of SI.…”
Section: Introductionmentioning
confidence: 99%
“…If the distribution of propagation directions is not isotropic the NCFs are asymmetric and represent a poorer approximation of the Green's function. Practically the coda of earthquake records and ambient seismic noise can be used as source wavefield for SI (Campillo 2006;Larose et al 2006) as was first demonstrated by Campillo & Paul (2003) and Shapiro et al (2005). By extracting surface waves (Brenguier et al 2007;Lin et al 2009;Stehly et al 2009) or body waves (Roux 2005;Tonegawa et al 2009;Zhan et al 2010;Poli et al 2012;Lin et al 2013;Nishida 2013) local, regional and global tomographic investigations of the subsurface velocity are among the most widely used applications of SI.…”
Section: Introductionmentioning
confidence: 99%
“…Derode et al, 2003) y en sismología (Campillo y Paul, 2003) muestran que tal correlación extrae la llamada FGE (la señal que se registraría en una estación como si una fuerza impulsiva fuera aplicada en la otra estación o viceversa). El uso de microtremores, o ruido sísmico ambiental, para recobrar la FGE entre pares de receptores ha sido muy popular en los últimos años (Larose et al, 2006, Curtis et al, 2006Sneider y Wapenaar, 2010;Campillo et al, 2011;Sneider y Larose, 2013). La identificación del tiempo de viaje (máximo del pulso de correlación) entre el par de receptores puede entonces ser utilizado para elaborar un imagen de tomografía que proporciona la distribución de la velocidad del medio que separa dos receptores (Shapiro y Campillo, 2004 5.…”
Section: Tomografía De Interferometría Sísmicaunclassified
“…The random locations of sources insure that the noise has uniform angular coverage, which will enhance the accuracy of the empirical Green's function computed by cross-correlation. In cases of non-uniform angular coverage, scatterers within the random media can enhance the angular coverage and, therefore, improve the accuracy of the empirical Green's functions (Larose et al 2006).…”
Section: Ambient-noise Simulationmentioning
confidence: 99%